Fodor's South Florida 2026 - Liss, Sara, 1979- (Fodor's Travel, a division of MH Sub I, LLC, 2026)
"Whether you want to snorkel in the Keys, party on Miami Beach, or tour the Everglades, the local Fodor's travel experts in South Florida are here to help! Fodor's South Florida: With Miami, Fort Lauderdale, and the Keys guidebook is packed with maps, carefully curated recommendations, and everything else you need to simplify your trip-planning process and make the most of your time. This new edition has been fully-redesigned with an easy-to-read layout, fresh information, and beautiful color photos."--Publisher.